Design and analysis of peaking capacitor for generation of high voltage fast risetime pulses - Madhu Palati; Manjunatha Babu Pattabhi; Ozwin Dominic Dsouza (Institute of Advanced Engineering and Science, 2026)
High voltage pulses of short duration are required in certain applications, here precise and rapid electrical energy delivery is required. These include applications like pulsed power system, high speed switching circuits, plasma generation circuits, high speed imaging, non-thermal food processing. One of the best and cheap methods of producing the high voltage fast rise time pulses is using Peaking capacitor. Designing a high-voltage peaking capacitor requires careful consideration of various factors such as voltage rating, capacitance value, energy storage capacity, physical size, dielectric material, and safety measures. In this paper, designing of 200 pF, 300 kV peaking capacitor is presented and simulation is carried out in PSPICE. The maximum peak voltage across the peaking capacitor, the time to reach peak voltage, and the maximum peaking current obtained are 290 kV, 98.9 ns, and 22.41 kA, respectively. Also, to study the electric field of the medium used in peaking capacitors, Quick field software is used. The maximum electric field in Perspex, used as a dielectric medium, was 13 kV/mm.